1988
DOI: 10.1161/01.hyp.12.1.46
|View full text |Cite
|
Sign up to set email alerts
|

Thromboxane and vascular smooth muscle cell growth in genetically hypertensive rats.

Abstract: SUMMARYThe vascular wall has the capacity to produce thromboxane A 2 . However, the role of vascular thromboxane A 2 is still uncertain. In this study, we examined the relationship between vascular thromboxane A 2 generation and vascular smooth muscle cell growth in spontaneously hypertensive rats (SHR). Vascular thromboxane A 2 generation was significantly enhanced by 49% in 5-week-old and by 117% in 15-week-old SHR as compared with age-matched Wistar-Kyoto rats (WKY). Thromboxane in the prehypertensive stage… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
14
0

Year Published

1990
1990
2016
2016

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 59 publications
(15 citation statements)
references
References 26 publications
1
14
0
Order By: Relevance
“…15,16) It has been pointed out that the growth of cardiovascular cells is enhanced in SHR and that hypertrophy of cardiovascular tissues and organs develops before blood pressure elevation. [29][30][31][32] In the present study, the long-term therapy with CS prevented the increase in left ventricular mass and fibrosis of left ventricular tissue. This prevention of cardiac fibrosis, combined with inhibition of cardiac hypertrophy, may account for the observed preservation of myocardial contractility and distensibility.…”
Section: Discussionsupporting
confidence: 54%
“…15,16) It has been pointed out that the growth of cardiovascular cells is enhanced in SHR and that hypertrophy of cardiovascular tissues and organs develops before blood pressure elevation. [29][30][31][32] In the present study, the long-term therapy with CS prevented the increase in left ventricular mass and fibrosis of left ventricular tissue. This prevention of cardiac fibrosis, combined with inhibition of cardiac hypertrophy, may account for the observed preservation of myocardial contractility and distensibility.…”
Section: Discussionsupporting
confidence: 54%
“…In addition to platelet activation, TxA2 or TP receptor is also known to promote cell migration and proliferation of vascular smooth muscle cells (VSMCs) (15)(16)(17)(18)(19)(20), an important process that is involved in a number of vascular diseases, such as postangioplasty restenosis and atherosclerosis (21). The proliferative response of VSMCs to vascular injury is markedly exaggerated in transgenic mice with vascular overexpression of the human TP␣ receptor, which can be inhibited by the TP-specific antagonist S18886 (6).…”
Section: Tp-specific Agonists [1s-[1␣2␣(z)3␤(1e3s*)4 ␣]]-7-[3-[3-mentioning
confidence: 99%
“…Prostacyclin was without effect, at concentrations up to 100 fiM, on the restimulation of growth in quiescent bovine aortic smooth muscle cells. 123 Ishimitsu et al 105 - 106 have shown that a stable thromboxane A 2 analogue, 9,ll-epithio-ll,12-methanothromboxane A 2 , dose-dependenth/ stimulates the incorporation of pHJthymidine into DNA of rat thoracic aortic smooth muscle cells, with a maximal effect at a concentration of 10 pM. This concentration also significantly prolonged the doubling time.…”
Section: Eicosanoidsmentioning
confidence: 99%